Moving consensus and managing expectations: media and REDD+ in Indonesia - Cronin, T.; Santoso, L.; Gregorio, M. di; Brockhaus, Maria; Mardiah, S.; Muharrom, E. (Springer, 2016)
This paper investigates policy actors’ positions on reducing emissions from deforestation and forest degradation (REDD+) expressed in Indonesian media, and shows how these policy debates have evolved between 2007 and 2012. Results indicate media debates have moved beyond early, buoyant consensus on REDD+ as a win-win solution for economic growth and environmental conservation, to clearly acknowledge the need for institutional and governance reform. Several shifts in the frequency and nature of REDD+ discourse around 2010 – including from an international to a national level focus and an increase in the level of optimism – suggests the 2010 Letter of Intent between Indonesia and Norway has the potential to be a significant driver of change. Results also indicate that translating political will into measurable performance at a local or jurisdictional level is likely to require a broader appreciation of the complex interests, expectations and implications associated with the necessary reforms, and stronger engagement with key actor groups whose vested interests go beyond REDD+ itself. We observe an apparent desire on the part of Indonesian national authorities to have their cake and eat it too; that is, to keep their forest and clear it too.